A comparison of mosquito densities, weather and infection rates of Aedes aegypti during the first epidemics of Chikungunya (2014) and Zika (2016) in areas with and without vector control in Puerto Rico. Issue 1 (17th September 2018) - Barrera, R.; Amador, M.; Acevedo, V.; Beltran, M.; Muñoz, J. L.
Abstract: In Puerto Rico, the first records of the transmission of Chikungunya (CHIKV) and Zika (ZIKV) viruses were confirmed in May 2014 and December 2015, respectively. Transmission of CHIKV peaked in September 2014, whereas that of ZIKV peaked in August 2016. The emergence of these mosquito‐transmitted arboviruses in the context of a lack of human population immunity allowed observations of whether the outbreaks were associated with Aedes aegypti (Diptera: Culicidae) densities and weather. Mosquito density was monitored weekly in four communities using sentinel autocidal gravid ovitraps (AGO traps) during 2016 in order to provide data to be compared with the findings of a previous study carried out during the 2014 CHIKV epidemic. Findings in two communities protected against Ae. aegypti using mass AGO trapping (three traps per house in most houses) were compared with those in two nearby communities without vector control. Mosquito pools were collected to detect viral RNA of ZIKV, CHIKV and dengue virus. In areas without vector control, mosquito densities and rates of ZIKV detection in 2016 were significantly higher, similarly to those observed for CHIKV in 2014. The density of Ae. aegypti in treated sites was less than two females/trap/week, which is similar to the putative adult female threshold for CHIKV transmission. No significant differences in mosquito density or infection rates with ZIKV and CHIKV at the same sites between years were observed. Although 2016 was significantly wetter, mosquito densities were similar. Abstract : In Puerto Rico, mosquito densities and rates of Zika virus (ZIKV) detection in 2016 were significantly higher in areas without vector control, similarly to those observed for Chikungunya virus (CHIKV) in 2014. The density of Aedes aegypti in sites treated with mass trapping was under two females/trap/week, which is similar to the putative adult female threshold for CHIKV transmission. There were no significant differences in mosquito density or infection rates with ZIKV and CHIKV at the same sites between years.